Tantangan Literasi dan Inklusi Dana Pensiun serta Dampaknya terhadap Ekonomi Nasional dan Generasi Tua di Indonesia - Syarifudin Yunus; Farid Nabil Elsyarif (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
A study on the challenges of pension fund literacy and inclusion in Indonesia concluded that the average level of pension fund literacy in the period 2013 - 2025 only reached 18.08%, while the average level of inclusion in that period only reached 4.23%. The level of pension fund literacy and inclusion in Indonesia is low. In SNLIK 2025, the pension fund literacy rate was 27.79%, while the pension fund inclusion rate was 5.37%. Compared to the 2022 pension literacy rate of 30.46% and the 2022 inclusion rate of 5.40%, this means that pension literacy and inclusion rates are declining. It can be said that out of 10 Indonesians, only 2.7 people “understand” pension funds and only 0.5 (half) people “have” pension funds. This means that for every 10 Indonesians, less than 1 person has a pension fund. Low pension literacy and inclusion has a direct impact in the form of 1) an older generation at risk of poverty or financial dependence on children/family, 2) a continuing sandwich generation cycle, 3) stagnant growth of the pension fund industry, 4) low public trust, and 5) the emergence of public skepticism towards pension funds in the future.